A Liturgical Play for the Medieval Feast of Fools : The Laon Ordo Joseph. - Lagueux, Robert C. (Boydell & Brewer, Inc, 2023)
A newly identified medieval play for the Feast of Fools, with a new English translation and musical edition ready for performance.